PEMANFAATAN TEPUNG DAUN KELOR MUDA (MORINGA OLEIFERA) SEBAGAI BAHAN BAKU PAKAN BUATAN PADA BUDIDAYA IKAN MAS (Cyprinus Carpio) - Duri Kelao Naria; Salnida Yuniarti Lumbessy; Dewi Putri Lestari (Journal of Fish Nutrition, 2022)
Carp (Cyprinus carpio) is one type of consumption fish which is a freshwater fishery commodity that has good prospects. The purpose of this study was to analyze the effect of using young Moringa leaf flour (Moringa oleifera) as raw material for artificial feed on carp (Cyprinus carpio) cultivation. The research method used was a completely randomized design (CRD) consisting of 4 treatments and 3 replications, treatment P1 (control), P2 (10% Moringa leaf flour), P3 (20% Moringa leaf flour), P4 (30% Moringa leaf flour). moringa). The results showed that the addition of Moringa leaf powder to feed with different doses could affect absolute weight, FCR, EPP and survival of carp (Cyprinus carpio) but did not affect absolute length and specific growth rate. The addition of 30% Moringa leaf flour to carp feed is the best treatment, because it can provide an absolute weight of 5.09 g, FCR of 1.86%, EPP of 53.95% and SR of 86.67% in carp culture.